Were there any tells in the Coţofeni culture area? - Cristian Ioan Popa (Българско е-Списание за Археология)
The approach to the topic of tells in the North-Danube area, between 3500 and 2800 BC, corresponding to the Coţofeni culture (in Bulgaria, Magura–Coţofeni, Tărnava culture) has been inconsistent. This study aims to clarify a series of archaeological and terminological aspects in direct relation to those Coţofeni sites that may or may not be included in the category of tell settlements. The so-called tell settlements are also discussed and the term pseudo-tell is proposed. Sites at very high altitudes (over 1000 m) or others related to salt exploitation have generated complex stratigraphies, consisting of successive Coţofeni levels, but completely different from the types of sediments that led to the formation of “classic” tells from the lowlands. The lack of fortifications is another feature of these settlements, which takes them away from the classic definition of a tell. Following this analysis, it can be summarized that the terminological problems or the established conventions are not sufficient to define certain Coţofeni sites, such as those from Ostrovu Corbului, Basarabi or Moldova Veche. However, there are arguments to speak of ​​tell or pseudo-tell settlements in the Coţofeni area. Compared to the impressive number of known sites in the area (over 1500), their percentage is only around 1%.